PENGARUH PROGRAM CORPORATE PHILANTROPHY AKSI 1000 SAHABAT NEGERI PT. RETAIL ESTATE SOLUTION TERHADAP CITRA PERUSAHAAN - Andella, Mellia (Jurnal Visi Komunikasi, 2019)
Imagery is defined as the public perception of their thoughts, beliefs, feelings and knowledge society itself against the company. Image is formed based on the knowledge and information received by someone. The information disseminated through communication in a program, one of which is a corporate social responsibility program. Previous research and Hsu Chiu reveals that aspects of CSR can affect the image of a product or company. One of the CSR program which is run by the Living World in maintaining the public image and the public welfare is corporate philanthropic program. Wibisono describes 4 stages of CSR management that are commonly used by companies, namely, planning, implementation phase, evaluation phase and reporting phase. The paradigm of research is positivism. This type of research used by the researchers is an explanatory with quantitative approach. The method used in the research by using quantitative methods by means of a survey by distributing questionnaires to the respondents with a sample of 94 people. Variable X has a strong positive correlation to the variable Y and a significant association with the coefficient of determination 0.396 (39.6%), which means Corporate Philanthropy Program affects the image of the Company amounted to 39.6%. The results of hypothesis testing there is significant influence between Corporate Philanthropy Program of Action 1000 Friends Neger PT. Retail Estate Solution to the Corporate Image.